Anti-tumor Activity of Triolimus: A Novel Multi-Drug Loaded Micelle Containing Paclitaxel, Rapamycin and 17-AAG - Hasenstein, Jason R. (2012)
Triolimus is a first-in-class, multi-drug loaded micelle containing paclitaxel, rapamycin and 17-AAG. In this study, we examine the anti-tumor mechanisms of action, efficacy and toxicity of Triolimus in vitro and in vivo. In vitro cytotoxicity testing of Triolimus was conducted using two aggressive adenocarcinomas including the lung cancer cell line, A549, and breast cancer cell line, MDA-MB-231. The three-drug combination of paclitaxel, rapamycin and 17-AAG displayed potent cytotoxic synergy in both A549 and MDA-MB-231 cell lines. Mechanistically, the drug combination inhibited both the Ras/Raf/MAPK and PI3K/Akt/mTOR pathways. Triolimus was advanced into tumor xenograft models for assessment of efficacy, toxicity and mechanisms of action. In vivo, a three-infusion schedule of Triolimus inhibited A549 and MDA-MB-231 tumor growth far more potently than paclitaxel-containing micelles and effected tumor cures in MDA-MB-231 tumor-bearing animals. Tumor growth delays resulted from a doubling in tumor cell apoptosis and a 50% reduction in tumor cell proliferation compared to paclitaxel-containing micelles. Enhanced anti-tumor efficacy was achieved without clinically significant increases in acute toxicity. Thus, Triolimus displays potent synergistic activity in vitro and anti-tumor activity in vivo with comparable toxicity to paclitaxel. These observations provide strong support for further development of Triolimus and an important proof of concept for safe, effective nanoparticle-based delivery of three complementary anti-cancer agents.